Odpowiedzi

2010-01-05T22:02:03+01:00
A) 3x+2=7
3x=7-2
3x=5/3
x=5/3
b) 7+3y=9
3y=9-7
3y=2/3

y=2/3
c) 3x(1-2w)-6=0
6x-6xw-6=0
6x(1-w)=6
6x=6
x=1
1-w=6
-w=5
w=-5
d) 6-(10-4t)=2
6-10+4t=2
4t=2+4
4t=6/4
t=6/4












1 5 1
2010-01-05T22:02:22+01:00
A) (3x+2)=7
3x=7-2
3x=5 /:3
x= 5/3 cztery trzecie 1i 2/3

B)7+(3y)=9
3y=9-7
3y=2/:3
y=2/3 dwie trzecie

D) 6-(10-4t)=2
6-10+4t=2
4t=2-6+10
4t=6/:4
t= 1.5
2010-01-05T22:05:05+01:00
A) (3x+2)=7
3x=7-2
3x=5/3
x=1⅔

B) 7+(3y)=9
3y=9-7
3y=2 /3
y=⅔


C) 3x(1-2w)-6=0
6x-6xw-6=0
6x(1-w)=6
6x=6
x=1
1-w=6
-w=5
w=-5

D) 6-(10-4t)=2
4t=2-6+10
4t=6/4
t=1½
1 5 1